A cross sectional study of depression during pregnancy and its risk factors among pregnant women attending a tertiary care hospital in Puducherry, India - P., Sabita; M., Prakash; E., Sharmila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Depression during pregnancy is a recognized global health issue which can lead to wide range of maternal and neonatal complications to extremes like maternal suicide to infanticide. This study was done to estimate the magnitude of depression during pregnancy and its risk factors among pregnant women attending a tertiary care hospital in Puducherry. Methods: A descriptive cross sectional study was done among 220 pregnant women attending routine antenatal checkup in outpatient department of a tertiary care hospital in Puducherry, using a systematic random sampling technique. A semi structured questionnaire using Patient Health Questionnaire-9 was used to screen the mothers for antenatal depression. Results: 220 pregnant women were evaluated for antenatal depression. Mean age of the study participants was 25.02±3.13 years. Using PHQ-9 authors found that 19.5% pregnant women were having risk for antenatal depression, of which the mild, moderate and moderately severe levels of depression were 16.4%, 1.4% and 1.8% respectively. The risk of antenatal depression was statistically significant among the women age more than 30 years, husband’s educational status as higher secondary and below, residence in rural area, multigravida, having a male child, strained relationship, no support during pregnancy and pressure for a male child. Logistic regression analysis revealed age ≥30 years (aOR 3.03, 95% CI 1.04-8.82), and no support during pregnancy (aOR 3.30, 95% CI 1.10-9.90) were the significant factors. Conclusions: Since the risk for antepartum depression is huge in this region, there is a need for screening for antepartum depression as a routine antenatal checkup in the out patient department. Reinforcing the importance of appropriate for conception and support for the mother during pregnancy plays a vital role in reducing the magnitude of this depression.